2012
DOI: 10.4028/www.scientific.net/jera.8.17
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Studies on Timber Data from Nigerian Grown Iroko Tree (<i>Chlorophora excelsa</i>) as Bridge Beam Material

Abstract: This paper provides the results of structural reliability analysis carried out on the data of Nigerian grown Iroko tree (Chlorophora excelsa), to ascertain its structural performance as timber bridge beams. Five pieces of 50mm x 75mm x 3600mm of Nigerian grown Iroko hardwood were bought, seasoned naturally and 200 pieces of samples were prepared for determination of their strength properties, (which include bending strength parallel to grain, tensile strength parallel to grain, compressive strength parallel to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…However, it is obvious that the Nigerian grown Abura timber is not safe in shear as bridge beam under the stated design conditions. This explains why each timber specie should be subjected to structural reliability analysis because Aguwa and Sadiku (2012) reported that the Nigerian grown Ekki timber in shear is reliable under the same design conditions. The reliability of the Nigerian grown Abura timber in shear can be improved if satisfactory dimensions are chosen by decreasing the span and increasing the depth of the beam.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, it is obvious that the Nigerian grown Abura timber is not safe in shear as bridge beam under the stated design conditions. This explains why each timber specie should be subjected to structural reliability analysis because Aguwa and Sadiku (2012) reported that the Nigerian grown Ekki timber in shear is reliable under the same design conditions. The reliability of the Nigerian grown Abura timber in shear can be improved if satisfactory dimensions are chosen by decreasing the span and increasing the depth of the beam.…”
Section: Discussionmentioning
confidence: 98%
“…The natural seasoning was preferred to artificial seasoning which is faster because the proposed timber structure is bridge, which is always completely exposed to natural weather conditions (Aguwa and Sadiku, 2012) Twenty (20) test specimens were used each for compression and shear respectively. The Universal Testing Machine (UTM) used has a capacity of 50kN and was in good working condition.…”
Section: Methods Of Testingmentioning
confidence: 99%
“…This decrease of safety index (๏ข) of the magnifier for the design of rectangular short column under biaxial bending implies a decrease of the reliability of the column designed using the magnifiers of [15]. This decrease in the reliability index could be attributed to the fact that the carrying capacity of the structural element is being exceeded thereby leading to the chances of failure [31]. A maximum of 5 kN/m 2 live load was adequately sustained by the column at the specified loading and geometric properties.…”
Section: Resultsmentioning
confidence: 99%
“…These names can be confusing since some softwoods exhibits greater strength properties than some hardwoods and vice versa (Ohagwu & Ugwuishiwu, 2011). Subjecting Nigerian grown timbers to engineering investigations is to establish adequate data and sufficient information for it to be adequately managed and help in building more confidence in identifying their specific areas of usage for structural safety (Aguwa et al, 2015;Mohammed, 2017;Rahmon & Jimoh, 2020). This is expected to lessen the over-dependence on foreign materials for structural applications and to create more employment opportunities that will impact the country's economy (Aguwa et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Subjecting Nigerian grown timbers to engineering investigations is to establish adequate data and sufficient information for it to be adequately managed and help in building more confidence in identifying their specific areas of usage for structural safety (Aguwa et al, 2015;Mohammed, 2017;Rahmon & Jimoh, 2020). This is expected to lessen the over-dependence on foreign materials for structural applications and to create more employment opportunities that will impact the country's economy (Aguwa et al, 2015). The development of local contents has to be encouraged towards infrastructural developments in developing countries like Nigeria using sustainable and environmentallyresponsive approach (Bakar et al, 2004;Aguwa & Sadiku, 2011).…”
Section: Introductionmentioning
confidence: 99%